Pediatric Dysgerminoma: Unveiling a Rare Ovarian Tumor - Limaiem, Faten; Saffar, Khalil; Halouani, Ahmed (Archives of Case Reports, 2024)
Background: Dysgerminomas, account for only 1% - 2% of all malignant ovarian neoplasms. Objective: This case report aims to present a rare occurrence of dysgerminoma in a pediatric patient, highlighting the clinical characteristics, diagnosis, and management. Case presentation: We present a case of dysgerminoma in a 12-year-old girl who presented with a three-week history of pelvic pain and progressive abdominal swelling. Physical examination revealed a distended abdomen with evident suprapubic fullness, and a palpable abdominopelvic mass measuring approximately 20 weeks in size. Imaging studies confirmed the presence of a solid heterogeneous mass originating from the pelvis. The patient underwent a right salpingo-oophorectomy without complications. Histological examination coupled with an immunohistochemical study confirmed the diagnosis of dysgerminoma. The patient had an uneventful postoperative course and was discharged without adjuvant treatment. Regular follow-up visits, physical examinations, ultrasound scans, and lactate dehydrogenase assays were initiated for monitoring. Conclusion: Prompt recognition and appropriate surgical intervention, followed by regular monitoring, are crucial for optimal outcomes in pediatric dysgerminoma cases.